An Analysis of the In-Store Customer Journey as a Strategy for Customer Experience Development - Nadira, Sofia; Darma, Gede Sri (Universitas Pendidikan Ganesha, 2025)
Offline retail stores face increasing challenges in integrating technology to enhance the customer journey and overall customer experience. This study employed a descriptive qualitative method with a phenomenological approach to examine touchpoints in the customer journey at offline stores, focusing on the use of technology as a development strategy. Data were collected through interviews with 12 informants who had experience shopping in both offline and online stores, and through questionnaires distributed to 137 respondents to assess consumer demand for technology in offline retail environments. The findings revealed that all respondents experienced five key stages in the customer journey at offline stores—awareness, consideration, search, purchase, and loyalty—which were categorized into three service phases: pre-service, service, and post-service. At the awareness stage, store display touchpoints emphasized both atmospheric and technological elements, such as LED screens and digital catalog tablets. During the consideration stage, displays focused on atmospheric, communicative, technological, and interactional elements, supported by a comfortable store layout and tablets. At the search stage, the fitting room area highlighted product interaction, process, and communication, incorporating Augmented Reality or interactive services. At the purchase stage, cashier touchpoints prioritized process and technology through self-checkout systems and multiple digital payment options. In the loyalty stage, membership touchpoints focused on communicative and process elements. Overall, the results indicated that strategically incorporating technology at each stage of the offline customer journey can enhance customer experience and foster long-term loyalty.